Etiology, diagnosis and treatment of lumbar disc degeneration: a focus on the mechanism of action of Piezo1 and research perspectives - Gong, Yan; Cheng, Zhaojun; He, Jiahui; Gan, Yanchi; Jiang, Xiaobing; Liu, Jintao (Frontiers in Cell and Developmental Biology, 2026)
Lumbar disc degeneration (LDD) is a chronic degenerative disease caused by the interaction of genetic and environmental factors, which mainly leads to lower back pain. Its early-stage lesions are insidious and lack reliable biomarkers, and the current diagnosis relies on imaging. Piezo1, a mechanosensitive ion channel widely expressed by intervertebral disc cells, is a core molecule that senses mechanical signals. As a core load-bearing structure of the spine, the mechanical responsiveness of the intervertebral disc is critical for homeostasis, and abnormal mechanical loading is a key trigger of LDD. Piezo1 is deeply involved in the pathology of LDD by sensing abnormal stress and mediating Ca2+ influx. On the one hand, activation of the Piezo1-Ca2+ axis triggers inflammatory pathways such as NF-κB and the upregulation of proinflammatory factors and matrix-degrading enzymes (e.g., MMPs, ADAMTS); on the other hand, it inhibits the synthesis of the extracellular matrix (ECM), such as type II collagen and proteoglycans, and promotes apoptosis and senescence. The “hypersensitive state” of degenerated discs, in which Piezo1 expression and activity are significantly elevated, is the core link between the transduction and amplification of mechanical signals and pathological cascades. By systematically reviewing the structure and function of Piezo1 and its regulatory mechanism in LDD, we aimed to clarify its role as a core mechanosensing molecule in degeneration and provide theoretical basis for new prevention and treatment strategies.